Effects of general relativity on glitch amplitudes and pulsar mass upper bounds. Issue 4 (26th January 2018) - Antonelli, M; Montoli, A; Pizzochero, P M
Abstract: Pinning of vortex lines in the inner crust of a spinning neutron star may be the mechanism that enhances the differential rotation of the internal neutron superfluid, making it possible to freeze some amount of angular momentum which eventually can be released, thus causing a pulsar glitch. We investigate the general relativistic corrections to pulsar glitch amplitudes in the slow-rotation approximation, consistently with the stratified structure of the star. We thus provide a relativistic generalization of a previous Newtonian model that was recently used to estimate upper bounds on the masses of glitching pulsars. We find that the effect of general relativity on the glitch amplitudes obtained by emptying the whole angular momentum reservoir is less than 30 per cent. Moreover, we show that the Newtonian upper bounds on the masses of large glitchers obtained from observations of their maximum recorded event differ by less than a few percent from those calculated within the relativistic framework. This work can also serve as a basis to construct more sophisticated models of angular momentum reservoir in a relativistic context: in particular, we present two alternative scenarios for macroscopically rigid and slack pinned vortex lines, and we generalize the Feynman–Onsager relation to the case when both entrainment coupling between the fluids and a strong axisymmetric gravitational field are present.